2018
DOI: 10.1192/bjp.2018.152
|View full text |Cite
|
Sign up to set email alerts
|

Clozapine is associated with secondary antibody deficiency

Abstract: Clozapine use was associated with significantly reduced immunoglobulin levels and an increased proportion of patients using more than five antibiotic courses in a year. Antibody testing is not included in existing clozapine monitoring programmes but may represent a mechanistic explanation and modifiable risk factor for the increased rates of pneumonia and sepsis-related mortality previously reported in this vulnerable cohort.Declaration of interestS.J. has received support from CSL Behring, Shire, LFB, Biotest… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

4
81
2
10

Year Published

2018
2018
2024
2024

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 64 publications
(97 citation statements)
references
References 27 publications
(44 reference statements)
4
81
2
10
Order By: Relevance
“…25 In a British case-control study, a higher proportion of the clozapine-treated group reported taking more than five courses of antibiotics in the preceding year, 5.3% (5/123) vs 1% (1/111) in controls taking other antipsychotics, and this was associated with an increased percentage of patients with low values for all immunoglobulins. 26 In an vitro study, clozapine increased the production of the interleukin-1 receptor antagonist. 27 Regarding possible increased infection risk in the absence of agranulocytosis, we only recommend that clinicians tell clozapine patients to avoid close contact with contagious people.…”
Section: Inflammation Can Increase Clozapine Levelsmentioning
confidence: 99%
“…25 In a British case-control study, a higher proportion of the clozapine-treated group reported taking more than five courses of antibiotics in the preceding year, 5.3% (5/123) vs 1% (1/111) in controls taking other antipsychotics, and this was associated with an increased percentage of patients with low values for all immunoglobulins. 26 In an vitro study, clozapine increased the production of the interleukin-1 receptor antagonist. 27 Regarding possible increased infection risk in the absence of agranulocytosis, we only recommend that clinicians tell clozapine patients to avoid close contact with contagious people.…”
Section: Inflammation Can Increase Clozapine Levelsmentioning
confidence: 99%
“…The lethality of pneumonia in clozapine patients is explained in that clozapine can contribute to pneumonia, and once pneumonia develops it can cause a clozapine intoxication; therefore, the combination of pneumonia and clozapine intoxication is highly lethal. This complex bidirectional association [162] is described in detail in online supplementary Box S7 [157,[163][164][165][166][167][168][169]. Our recommendations for decreasing the risk and lethality of pneumonia in clozapine patients are described in online supplementary Box S8 [65,162,170,171].…”
Section: Pneumoniamentioning
confidence: 99%
“…Various mechanisms have been proposed for the rise in pneumonia, including sedation, sialorrhoea and aspiration, agranulocytosis, and smoking 910. Following the introduction of calculated globulin screening in Wales,11 we found a novel and striking association between use of the antipsychotic clozapine and antibody deficiency 12. Patients taking clozapine follow an intensive regimen of blood testing for the rare risk of agranulocytosis (with cumulative incidence of <1% cases), but antibody testing is not included in existing clozapine monitoring programmes.…”
mentioning
confidence: 90%